2002
DOI: 10.1212/wnl.58.10.1505
|View full text |Cite
|
Sign up to set email alerts
|

Predicting surgical outcome in temporal lobe epilepsy patients using MRI and MRSI

Abstract: MR features are important markers of surgical outcome in patients with TLE and can provide assistance in identifying surgical candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 24 publications
2
26
2
2
Order By: Relevance
“…No full economic evaluation studies that met the inclusion criteria were identified. Four of the diagnostic accuracy studies, all by the same author, [86][87][88]91 and the five cohort studies [118][119][120][121][122] used regression analysis to assess the value of imaging findings in the prediction of outcome following surgery. The 75 studies on the diagnostic accuracy of imaging for the localisation of seizure focus included a total of 179 test evaluations.…”
Section: Results Of the Literature Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…No full economic evaluation studies that met the inclusion criteria were identified. Four of the diagnostic accuracy studies, all by the same author, [86][87][88]91 and the five cohort studies [118][119][120][121][122] used regression analysis to assess the value of imaging findings in the prediction of outcome following surgery. The 75 studies on the diagnostic accuracy of imaging for the localisation of seizure focus included a total of 179 test evaluations.…”
Section: Results Of the Literature Searchesmentioning
confidence: 99%
“…88 Three studies used logistic regression analysis, 87,120,121 using 2 tests for the univariate analysis for categorical data, and one study also used the rank sum test for continuous data. 121 One study used Bayesian classifiers to predict outcome following surgery based on conditional probability distributions, 118 one used discriminant analysis, 119 and the final study used a log-linear model to compare the predictive value of MRI with those of other test combinations. 122 One study was only reported as an abstract and so limited details were available.…”
Section: Association Of Seizure Focus Localisation With Outcome Follomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flow of studies through the review. Eighteen studies met the inclusion criteria (n = 1312; range 42,49,[55][56][57][58]61,[63][64][65][66]68,69 seven reported outcome prediction using either a multivariate regression analysis or Bayesian classifiers, 49,56,60,62,67,68,70 and one was a decision study. 59 Brief study details are provided in Table 4; full study details are provided in Appendix 3.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies 49,56,57,59,61,[63][64][65][66][67][68]70 (68%) reported follow-up of at least 12 months in all patients. Of the seven outcome prediction studies, four 60,62,68,70 (21%) reported dropouts to be similar across groups, one 49 (5%) reported surgical outcome assessment being blinded to test result, it was unclear in any outcome prediction study whether the groups were comparable on all important confounding factors, 71 and none adequately adjusted for its effects.…”
Section: Resultsmentioning
confidence: 99%